2013
DOI: 10.1002/jcb.24661
|View full text |Cite|
|
Sign up to set email alerts
|

Human Wharton's Jelly Stem Cells and Its Conditioned Medium Enhance Healing of Excisional and Diabetic Wounds

Abstract: Wound healing is a major problem in diabetic patients and current treatments have met with limited success. We evaluated the treatment of excisional and diabetic wounds using a stem cell isolated from the human umbilical cord Wharton's jelly (hWJSC) that shares unique properties with embryonic and adult mesenchymal stem cells. hWJSCs are non-controversial, available in abundance, hypo-immunogenic, non-tumorigenic, differentiate into keratinocytes, and secrete important molecules for tissue repair. When human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 57 publications
6
83
2
Order By: Relevance
“…On the other hand, other studies have revealed that transplanted MSCs do not necessarily have to be in close proximity to damaged tissue to promote wound repair and functional recovery, thereby suggesting that paracrine factor secretion is the main MSC therapeutic action concerned in repairing skin disorders [129,130]. This theory has been further reinforced by recent studies which have shown that allogeneic MSCs-conditioned medium has enhanced healing when administered locally into wounds [121,122,[131][132][133][134].…”
Section: Msc-related Therapy For Diabetic Woundsmentioning
confidence: 99%
“…On the other hand, other studies have revealed that transplanted MSCs do not necessarily have to be in close proximity to damaged tissue to promote wound repair and functional recovery, thereby suggesting that paracrine factor secretion is the main MSC therapeutic action concerned in repairing skin disorders [129,130]. This theory has been further reinforced by recent studies which have shown that allogeneic MSCs-conditioned medium has enhanced healing when administered locally into wounds [121,122,[131][132][133][134].…”
Section: Msc-related Therapy For Diabetic Woundsmentioning
confidence: 99%
“…There is a substantial amount of literature which investigate the beneficial effects of cellular therapy with WJ-MSCs, alone or within a scaffold (Zebardast et al, 2010; Azari et al, 2011; Shohara et al, 2012; Arno et al, 2014; Fong et al, 2014; Ribeiro et al, 2014; Sabapathy et al, 2014). Emerging reports are showing the promising role of decellularized biological matrices for tissue repair (Boccafoschi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Wharton's jelly-derived MSCs have the ability to maintain phenotypic attributes, cell growth kinetics, cell cycle pattern, in vitro multilineage differentiation plasticity, apoptotic pattern, normal karyotype-like intrinsic MSC properties in long-term in vitro cultures (Sabapathy et al, 2014). Several studies have investigated cellular therapy with WJ-MSCs, alone or within a scaffold (Azari et al, 2011; Shohara et al, 2012; Fong et al, 2014; Ribeiro et al, 2014; Sabapathy et al, 2014). Studies have elucidated the role of WJ-MSCs for various applications, such as for neurological disorders (Shalitin et al, 2003), kidney injury (Du et al, 2013), lung injury (Moodley et al, 2009), liver injury and cancer therapy (Sabapathy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…28 Stem cells derived from umbilical cord Wharton’s jelly show high proliferative capacity, can differentiate into the three germ lineages, are available in large numbers and have prolonged stemness characteristic‏. 29,30 These advantages combined with their non-controversial nature and non-tumorogenicity make them attractive cell source for cell-based therapy‏. 15 The exact mechanism by which WJ-SCs exert their function isn’t yet completely known but they can affect the other cell’s behavior through secretion of specific molecules such as cytokines and growth factors‏.…”
Section: Discussionmentioning
confidence: 99%